Investigating kurdish efl students’ speed reading and reading comprehension levels at the university of duhok - Sipan Mohammed; Fatimah Hasan (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2023)
The purpose of this study was to identify Kurdish EFL students’ speed reading and reading comprehension levels and to show the effect of speed reading on reading comprehension. The study utilized a quantitative method to collect data for a period of six weeks. The participants were 25 second-year students with intermediate level in the Departments of English, College of Languages, and College of Basic Education at the University of Duhok (hereafter: UoD). For assessing speed reading and reading comprehension level, Well Read 3 was adapted since it is intended for intermediate level. After the pretest, the participants were trained by speed reading techniques in order to improve their speed reading and reading comprehension. The pretest and posttest results demonstrated that the total average students' speed reading and reading comprehension levels were significantly increased. Furthermore, the result obtained from the regression analysis showed a significant influence of speed reading on reading comprehension. Due to the constant change occurring in speed reading, reading comprehension changed interchangeably by 25%. In only a period of six weeks, the findings of this research could confirm the need to integrate speed reading courses in all educational levels.